2021
DOI: 10.1101/2021.03.09.434693
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Psychomotor Impairments and Therapeutic Implications Revealed by a Mutation Associated with Infantile Parkinsonism-Dystonia

Abstract: Parkinson's disease (PD) is a neurodegenerative disorder affecting over 6.1 million people worldwide. Studies of highly-penetrant mutations identified in early-onset familial parkinsonism have contributed to our understanding of the mechanisms underlying PD. Dopamine (DA) transporter (DAT) deficiency syndrome (DTDS) is a type of infantile parkinsonism-dystonia that shares clinical features with PD. Here, we define structural, functional, and behavioral consequences of a Cys substitution at R445 in human DAT (h… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 120 publications
0
7
0
Order By: Relevance
“…These conformers occasionally gave rise to simultaneous opening of both the EC and IC gates such that an intermittent formation of a water channel was detected. Notably, the sodium permeation path (Aguilar et al, 2021) coincides with that of water channeling (Cheng et al, 2018;Cheng and Bahar, 2019). This path, observed in silico, may also be associated with DATmediated ion fluxes or leak currents (Ingram et al, 2002;Erreger et al, 2008).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…These conformers occasionally gave rise to simultaneous opening of both the EC and IC gates such that an intermittent formation of a water channel was detected. Notably, the sodium permeation path (Aguilar et al, 2021) coincides with that of water channeling (Cheng et al, 2018;Cheng and Bahar, 2019). This path, observed in silico, may also be associated with DATmediated ion fluxes or leak currents (Ingram et al, 2002;Erreger et al, 2008).…”
Section: Discussionmentioning
confidence: 62%
“…Recently, molecular modeling found that the infantile Parkinsonism-Dystonia associated substitution, R445C in hDAT, disrupted a phylogenetically conserved intracellular network of interactions and promoted a channel-like intermediate of hDAT. These rearrangements lead to the permeation of Na + from both the EC and IC solutions (Aguilar et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Drosophila is a powerful model system to determine in vivo processes underlying altered DA function due to its conserved mechanisms of DA neurotransmission [56][57] and its genetic tractability. We utilized the fmn Drosophila (DAT fmn ) background, which lacks expression of full-length Drosophila DAT (dDAT) and serves as a functional knock out 58 , in combination with phiC31-based integration to insert a UAS-driven hDAT WT or hDAT SD to express these hDAT constructs specifically in DA neurons, as previously shown [10][11]59 . We utilized this model system to define the role played by hDAT N-terminus and Stx1 phosphorylation in AMPH-induced DA efflux ex vivo and AMPH-associated behaviors 11,55 .…”
Section: Cde Occurs In Drosophila Brainmentioning
confidence: 99%
“…These agents markedly enhance extracellular DA through their actions as DAT inhibitors (cocaine, methylphenidate) and substrates (AMPH). Moreover, multiple DAT coding variants have been reported in probands from ADHD, and autism spectrum disorder (ASD) patients (914), as well as in DAT deficiency syndrome, a form of Parkinsonism (1519). Given that DAT function profoundly impacts DAergic signaling, it is vital that we understand the molecular mechanisms that acutely regulate DAT availability.…”
Section: Introductionmentioning
confidence: 99%
“…These agents markedly enhance extracellular DA through their actions as DAT inhibitors (cocaine, methylphenidate) and substrates (AMPH). Moreover, multiple DAT coding variants have been reported in probands from ADHD, and autism spectrum disorder (ASD) patients [9][10][11][12][13][14] , as well as in DAT deficiency syndrome, a form of Parkinsonism [15][16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%